The Effect of Service Quality toward Customer Satisfaction in a Sharia Pawnshop (Case Study on a Sharia Pawnshop in Jambi Province) - Busriadi Busriadi (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Purpose: This research analyzes the business phenomenon of PT. Pegadaian Syariah (Persero) Tbk. in Jambi province, in which the problem is how to build customer satisfaction to achieve the company goal. This research is designed to analyze the effect of service quality on customer satisfaction. This research aims to find answers to the flow of service quality performance. In addition, the modeling in this study also aims to provide a critical understanding of the concept and measurement of customer relationship management.